Processes of global integration and the economic growth - Li-Jiuan, Chen-Rabich (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
The WTO is a member-driven international trade organization composed of governments and customs territories. It sets the legal framework for trade among the members. The EU as successor of the EC is the founding member since the establishment of the WTO in 1995. With the gradual enlargement process, the EU has been also one of the super members with the strong economic power within the WTO. Since the open and reform towards the world economy, China has taken a rapid step for the economic development in the 1980s. China has accessed into the WTO in Dec. 2001. The Taiwan’s economy strongly depends on export. Therefore, trade plays a very important role for Taiwan. Taiwan has become the 144th member of the WTO since 2002. Nowadays the WTO is an important platform for Taiwan in the international community, especially the Cross-Straits trade relation between China and Taiwan. With the trend of globalization, the trade relation between China and Taiwan is unavoidable and inevitable. The Cross-Straits trade relation has rapidly developed after their access into the WTO. As a result, the WTO has become an important platform for the interaction between China and Taiwan. Furthermore, China and Taiwan have concluded in 2009 the Economic Cooperation Framework Agreement (ECFA) under the WTO.This thesis firstly works on the ECFA as basis to explain its content and its impact on the both-side development. Secondly, it deals with the triangle relation among China, the EU and Taiwan within the WTO. Furthermore, it focuses on the signification of the ECFA for the triangle trade relation and its future. Finally, it draws a conclusion as finding of this research.